Nano-Selenium Alleviates Cadmium-Induced Acute Hepatic Toxicity by Decreasing Oxidative Stress and Activating the Nrf2 Pathway in Male Kunming Mice - Du, Hong; Zheng, Yilei; Zhang, Wei; Tang, Huaqiao; Jing, Bo; Li, Haohuan; Xu, Funeng; Lin, Juchun; Fu, Hualin; Chang, Lijen; Shu, Gang (Frontiers in Veterinary Science, 2022)
Cadmium (Cd) is known as a highly toxic heavy metal and has been reported to induce hepatotoxicity in animals. Nano-selenium (NSe) is an antioxidant that plays many biological roles such as oxidative stress alleviation. The purpose of this study is to explore the mechanism of action by which NSe inhibits Cd-induced hepatic toxicity and oxidative stress. Sixty eight-week-old male Kunming mice were randomly divided into four groups (15 mice per group). The control group and cadmium groups received distilled water, whereas the sodium-selenite group received 0.2 mg/kg SSe and the NSe group received 0.2 mg/kg NSe intragastrically for 2 weeks. On the last day, all the other groups were treated with Cd (126 mg/kg) except for the control group. The results obtained in this study showed that NSe alleviated Cd-induced hepatic pathological changes. Furthermore, NSe reduced the activities of ALT and AST as well as the content of MDA, while elevated the activities of T-AOC, T-SOD and GSH (P < 0.05). In addition, the NSe group significantly increased mRNA expressions of Nrf2 pathway related molecules (Nrf2, HO-1, NQO-1, GST, GSH-Px, CAT and SOD) compared to the Cd group (P < 0.05). In conclusion, NSe shows its potentiality to reduce Cd-induced liver injury by inhibiting oxidative stress and activating the Nrf2 pathway.